Design and evaluation of semi–active suspension control algorithms using hardware–in–the–loop simulations. (4th August 2014) - Hwang, S.H.; Heo, S.J.; Park, K.
The semi–active suspension system, due to capability of improving ride quality with low cost and light weight, is expected to be widely adopted in passenger vehicles in the near future. A key to the success is to develop controllers that enhance ride comfort over the passive suspension system without degrading driving safety. To this end, a practical controller for the semi–active suspension system with a continuously variable damper has been developed. The controller has been designed to quickly follow the desired damping force commands produced by the modified skyhook control algorithm. Trajectory optimisation has been performed to find the best control usage and performance limits of the semi–active suspension system. The designed control algorithm has been tested in a hardware–in–the–loop simulator, where the real–time vehicle dynamics software is coupled with the damper hardware via interface boards.